To condense the expression \( \ln 11 - 3 \ln p \), we can use the properties of logarithms. Specifically, we can utilize the property that states \( a \ln b = \ln(b^a) \) and the property that states \( \ln a - \ln b = \ln \left( \frac{a}{b} \right) \).
Starting with the expression:
\[ \ln 11 - 3 \ln p \]
We can first rewrite \( 3 \ln p \) using the property \( a \ln b = \ln(b^a) \):
\[ 3 \ln p = \ln(p^3) \]
So we replace \( 3 \ln p \) in the original expression:
\[ \ln 11 - 3 \ln p = \ln 11 - \ln(p^3) \]
Now, we can apply the property \( \ln a - \ln b = \ln \left( \frac{a}{b} \right) \):
\[ \ln 11 - \ln(p^3) = \ln \left( \frac{11}{p^3} \right) \]
Thus, the condensed form of \( \ln 11 - 3 \ln p \) is:
\[ \ln \left( \frac{11}{p^3} \right) \]